Current status of mosaic disease on patchouli and its control in Indonesia - Rita Noveriza (Perspektif, 2016)
ABSTRACKIn Indonesia, the patchouli plant has been developed in twenty one Province and now there are 10 provinces that would be the area of development of patchouli with an area of 150 ha and a seed garden is focused in North Sulawesi with an area of 6 hectares. Mosaic disease on patchouli has been developing very fast, within a period of 3 years have spread to the central cultivation of patchouli in Sumatera, Java and Sulawesi. This is mainly due to the multiplication of patchouli by vegetative cutting. Therefore, the use of virus-free seed patchouli and early detection methods of patchouli seed is a major concern. In addition, the maintenance of patchouli seeds in the nursery to be free of mosaic disease and its vector is very important. Sanitation and spraying the plants with formulation of clove and citronella oil needs to be done every one or two weeks to protect the seed patchouli in nursery and every four weeks in field.Keywords: Pogostemon cablin, Potyvirus, biopesticide, mosaic disease control. ABSTRAKStatus terkini penyakit mosaik pada tanaman nilan dan pengendaliannya di IndonesiaDi Indonesia, tanaman nilam telah dikembangkan di duapuluh satu Provinsi dan sekarang ada 10 provinsi yang akan menjadi daerah pengembangan nilam dengan luas 150 ha dan kebun bibit difokuskan di Sulawesi Utara dengan luas 6 hektar. Penyakit mosaik dari nilam telah berkembang sangat cepat, dalam jangka waktu 3 tahun telah menyebar ke budidaya pusat nilam di Sumatera, Jawa dan Sulawesi. Hal ini terutama disebabkan oleh perbanyakan nilam dengan memotong vegetatif. Oleh karena itu, penggunaan nilam benih bebas virus dan metode deteksi dini benih nilam merupakan perhatian utama. Selain itu, pemeliharaan bibit nilam di persemaian untuk bebas dari penyakit mosaik dan vektor yang sangat penting. Sanitasi dan penyemprotan tanaman dengan formulasi cengkeh dan minyak sereh perlu dilakukan setiap satu atau dua minggu untuk melindungi benih nilam di persemaian dan setiap empat minggu di lapangan.Kata kunci: Pogostemon cablin, Potyvirus, biopestisida, pengendalian penyakit mosaik.